2020
DOI: 10.3389/fphar.2020.00014
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Population Pharmacokinetics and Dosing Optimization of Cefepime in Neonates and Young Infants

Abstract: Objective: Cefepime is used to treat severe infections in neonates. Pharmacokinetic data have only been evaluated among preterm neonates and population pharmacokinetic model lacked external validation. Hence, our aim is to obtain the population pharmacokinetic parameters of cefepime with large sampling and optimize the cefepime dosage regimen for neonatal infection based on developmental pharmacokinetics-pharmacodynamics.Methods: Blood samples from neonates and young infants treated with cefepime were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 15 publications
(21 reference statements)
1
15
0
Order By: Relevance
“…A 2-compartment model best described our data, in accordance with previously published studies. [12][13][14] When normalizing PK parameters on our median weight of 4.5 kg for comparison, our CL was similar to values found in neonates (320-536 mL/h/4.5 kg), [14][15][16][17] while being lower than previously reported values in infants and children not supported with ECMO (500-900 mL/h/4.5 kg). 14,18 In addition to the young age of our cohort (median of 2.5 months), we believe our observed low CL may be explained by organ dysfunctions associated with critical illness.…”
Section: Discussionsupporting
confidence: 85%
“…A 2-compartment model best described our data, in accordance with previously published studies. [12][13][14] When normalizing PK parameters on our median weight of 4.5 kg for comparison, our CL was similar to values found in neonates (320-536 mL/h/4.5 kg), [14][15][16][17] while being lower than previously reported values in infants and children not supported with ECMO (500-900 mL/h/4.5 kg). 14,18 In addition to the young age of our cohort (median of 2.5 months), we believe our observed low CL may be explained by organ dysfunctions associated with critical illness.…”
Section: Discussionsupporting
confidence: 85%
“…Luckily, the combination of population pharmacokinetics and Monte Carlo simulation could be used to recommend the optimum initial regimen, which has been successfully used in many drugs. For example, Zhao et al reported developmental population pharmacokinetics and dosing optimization of cefepime in neonates and young infants (Zhao et al, 2020). Therefore, the present study aimed to recommend the initial dosage regimen for sirolimus improving drug blood level for seizure control in pediatric patients with TSC based on the population pharmacokinetics and Monte Carlo simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Opportunistic samples collected from blood remaining after routine laboratory tests as part of clinical care is one of the novel proposed methods 37,38 . However, the opportunistic‐sampling approach also poses issues, such as variability in available sample numbers among patients.…”
Section: Discussionmentioning
confidence: 99%
“…All rights reserved Opportunistic samples collected from blood remaining after routine laboratory tests as part of clinical care is one of the novel proposed methods. 37,38 However, the opportunistic-sampling approach also poses issues such as variability in available sample numbers among patients. The optimal-sampling approach used in the present study will help guide which blood sampling times' data should be noted.…”
Section: Accepted Articlementioning
confidence: 99%